Pemodelan Derajat Kesehatan Menggunakan Structural Equation Modeling di Kabupaten Kediri - tohari, amin (Fakultas Sains dan Teknologi Univ. PGRI Adi Buana Surabaya, 2017)
The health status of District Kediri in 2015 show that position of Maternal Mortality Rate is the same as the previous year, while the condition of Infant Mortality Rate tends to decrease compared to 2013. Health degree and influencing factors are latent variables requires an indicator to measure it, requiring a multivariate analysis method that accommodates the relationship between latent variables i.e. structural equation modeling (SEM). SEM-PLS can be used small sample size, and does not require normal multivariate distribution. This study uses secondary data taken from health office of District Kediri which summarized in health profile of Regency of Kediri in 2015, then processed using SmartPLS. The results showed that the environment, behavior of society, and health services have a negative and significant effect.